Students' Perceptions of the Use of Story Mapping in Reading Comprehension of Descriptive Text - Risti Nur Aini (Institut Agama Islam Negeri Palopo, 2024)
Story Mapping is a visual technique that helps students understand and organize information in descriptive text, improves reading comprehension, writing skills, and student engagement, but faces challenges such as variations in student abilities, time constraints, technological constraints, the crucial role of teachers, and the need for feedback and effective evaluation. The aim of this research is to determine students' perceptions of the use of story mapping in reading comprehension of descriptive text. The research used a qualitative approach to explore the perceptions of seventh grade students at SMP Negeri 1 Krembung Sidoarjo regarding the use of story maps in improving reading comprehension. The results of the research include: (1) Students' perceptions of the use of Story Mapping in reading comprehension of descriptive text are generally positive, because it helps visualize and organize information, although some students face challenges in its implementation; (2) The advantages of using Story Mapping for students' reading comprehension in the classroom include facilitating visual comprehension, increasing information retention, making it easier to organize information, helping in-depth analysis, and encouraging active student involvement; and (3) Difficulties in using Story Mapping for students' reading comprehension in the classroom including limited vocabulary, complexity of digital design, challenges in interpreting visualizations, incompatibility with individual learning styles, and difficulties in organizing information systematically.